Extending themselves : user-initiated transformations of government-built housing in developing countries - Tipple, A. Graham (Liverpool University Press, 2000)
Many countries have large stocks of government-built housing which, for various reasons, are in poor physical conditions and/or do not conform to the expectations of occupants. The occupants of such housing frequently make unauthorised but quite considerable changes and extensions (transformations) to their dwellings. This book examines user-initiated transformations to government-built housing in Bangladesh, Egypt, Ghana and Zimbabwe, surveyed in a research programme sponsored by the UK Department for International Development. The 1600 dwellings surveyed show how relatively low-income househ.